Culture and Literature in the 1970s - Proaño Arandi, Francisco (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
This chapter examines the cultural effervescence of the decade, marked by a shift from the momentum of the 1960s to a period of creative and critical retreat. It analyzes how the oil boom transformed urban lifestyles and strengthened the state’s presence in the arts, sparking debates about the “officialization” of culture. It highlights milestones such as *Between Marx and a Naked Woman*, the visual renewal of the VAN groups, and the consolidation of an essay that sought to diagnose national identity.